Review Perkembangan Formulasi Sediaan Pil Herbal: Tinjauan Literatur terhadap Teknologi Formulasi, Evaluasi Mutu, dan Potensi Terapi - Zakkiya Sabilla; Meiva Shafa Herdini; Elsa Tectona Zulianti; Renata Setya Agustin; Farrel Darian Hafiz Fathan; M Ilham Fannany; Maria Delsiana Ndun (CV. ITTC INDONESIA, 2026)
Pill dosage forms remain one of the most widely used traditional solid pharmaceutical preparations due to their good stability, ease of manufacturing, and suitability for herbal active ingredients. Advances in pharmaceutical technology have encouraged the optimization of pill formulations through the selection of excipients, manufacturing techniques, and quality evaluation to improve product performance and therapeutic effectiveness. This review aimed to summarize recent developments in herbal pill formulation based on published scientific literature. A literature review approach was conducted using articles retrieved from PubMed, Google Scholar, and other scientific databases. The review focused on turmeric (Curcuma longa) pills, Stenochlaena palustris herbal pills, and studies investigating the influence of binders, disintegrants, powder fineness, and drying conditions on pill quality. The reviewed studies demonstrated that formulation variables significantly affect weight uniformity, hardness, disintegration time, stability, and overall product quality. Continuous innovation in formulation strategies contributes to the development of herbal pills with improved pharmaceutical characteristics, enhanced stability, and better patient acceptance, supporting the modernization of traditional herbal dosage forms.